2003
DOI: 10.1016/s1569-1993(03)00025-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of vitamin K deficiency in CF—how much sophistication is useful?

Abstract: Vitamin K deficiency of liver or bone may occur independently. Prothrombin time is an insensitive marker. Individuals with ApoE4 allels might be more susceptible to osteopenia. As high expenditures are necessary to detect patients at risk, routine vitamin K supplementation for all PICF patients appears appropriate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 18 publications
0
19
0
2
Order By: Relevance
“…In EPI, lipase deficiency prevents breakdown of dietary triglycerides into monoglycerides and fatty acids, causing an inadequate solubilization and absorption of fat-soluble vitamins, including vitamin K. This produces vitamin K deficiency as described in humans (Edwards & Russel, 1987;Dutta et al ., 1982;Sinaasappel et al ., 2002;Mosler et al ., 2003). In dogs with EPI, malabsorption of fat-soluble vitamins may be suspected but the importance of vitamin A, vitamin D, vitamin E and vitamin K deficiency in dogs has not been reported (Westermarck et al ., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In EPI, lipase deficiency prevents breakdown of dietary triglycerides into monoglycerides and fatty acids, causing an inadequate solubilization and absorption of fat-soluble vitamins, including vitamin K. This produces vitamin K deficiency as described in humans (Edwards & Russel, 1987;Dutta et al ., 1982;Sinaasappel et al ., 2002;Mosler et al ., 2003). In dogs with EPI, malabsorption of fat-soluble vitamins may be suspected but the importance of vitamin A, vitamin D, vitamin E and vitamin K deficiency in dogs has not been reported (Westermarck et al ., 2005).…”
Section: Discussionmentioning
confidence: 99%
“…14 Mosler et al, demonstrated normal PIVKA-II concentrations only in two cases among 15 CF subjects with liver disease who were receiving oral ursodeoxycholic acid due to high GGT activity. 13 Rashid et al, and Wilson et al, documented pathological PIVKA-II concentrations in all CF patients with liver disease (n= 8 and n= 6, respectively). 31,34 Recently, we found evidence that vitamin K deficiency is more frequent in CF patients with liver cirrhosis than in those without.…”
Section: Clinical Biochemical and Functional Parameters In Cf Patimentioning
confidence: 93%
“…11,12 Vitamin K deficiency predisposes CF patients to easy bruising and bleeding (especially among infants), defective bone mineralization and osteoporosis. [13][14][15] R o u t i n e v i t a m i n K s u p p l e m e n t a t i o n in CF patients is recommended in many countries.…”
Section: Introductionmentioning
confidence: 99%
“…14 Mosler y col. demostraron concentraciones normales de PIVKA-II solamente en dos de 15 sujetos con FQ con hepatopatía que recibían ácido ursodesoxicólico por vía oral debido a una actividad elevada de la GGT. 13 Rashid y col. y Wilson y col., documentaron concentraciones patológicas de PIVKA-II en todos los pacientes con FQ y hepatopatía (n= 8 y n= 6, respectivamente). 31,34 Recientemente, se halló evidencia de que la deficiencia de vitamina K era más frecuente en los pacientes con FQ y cirrosis hepática que en aquellos que no la tenían.…”
Section: Tabla 5 Análisis De Regresión Múltiple Escalonada Hacia Adeunclassified
“…11,12 La deficiencia de vitamina K predispone a los pacientes con FQ a desarrollar hematomas y hemorragia fácilmente (en especial, en los lactantes), mineralización ósea deficiente y osteoporosis. [13][14][15] En muchos países, se recomienda el aporte suplementario habitual de vitamina K en los pacientes con FQ.…”
Section: Introductionunclassified